1998
DOI: 10.1007/s002239900428
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Diffraction on Cyclically Loaded Osteons

Abstract: The results of a study on the fine structural distortion due to the two previously observed types of degradation in cyclically loaded single osteons (i.e., stiffness degradation and pinching effect) are presented. Fully calcified longitudinal and alternate osteons were isolated from 350-microns-thick longitudinal sections of human femoral cortical bone. The samples were prepared from 500-microns-long central cylindrical portions of an osteon, whose two ends were penetrating into rectangular lugs for fixation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Since we cannot generally assume local fiber symmetry at a certain hierarchical level, a full 3D pole figure analysis of the 002 reflection is, in principle, necessary. Texture analysis in bone has already been employed since many years with x rays, [91][92][93][94] and neutrons, 95 but only little position resolved work on intact tissues has been reported so far. A comparison of the local crystallographic orientation of the mineral c axis with the morphological orientation of the mineral particles was recently undertaken in human trabecular bone.…”
Section: B Quantitative Texture Analysis In Bonementioning
confidence: 99%
“…Since we cannot generally assume local fiber symmetry at a certain hierarchical level, a full 3D pole figure analysis of the 002 reflection is, in principle, necessary. Texture analysis in bone has already been employed since many years with x rays, [91][92][93][94] and neutrons, 95 but only little position resolved work on intact tissues has been reported so far. A comparison of the local crystallographic orientation of the mineral c axis with the morphological orientation of the mineral particles was recently undertaken in human trabecular bone.…”
Section: B Quantitative Texture Analysis In Bonementioning
confidence: 99%
“…When single osteons are cyclically loaded, synchrotron x-ray diffraction measurements of the ͑averaged͒ mineral crystal orientation show that on average, reorientation of the c axis occurs in the direction of applied load parallel to the osteon axis. 10 Blood vessels, as the main transport system for oxygen, carbon dioxide, and several other elements, require a special protection inside the bone. Therefore the structure of an osteon has to fulfill this function.…”
Section: Introductionmentioning
confidence: 99%
“…Texture analysis can be used as a quantitative method for determining the crystal orientation in bone 10,12,13 Scanning x-ray experiments with a micrometer sized beam using high brilliance synchrotron radiation 14 enable the measurement of the local mineral orientation of entire osteons. Clearly, only the combination of: ͑a͒ a beamsize comparable to or smaller to the size of single lamellae; ͑b͒ a sample thickness of the same order of magnitude as the beam diameter ͑for transmission x-ray measurements͒; ͑c͒ stepwise rotation of the sample for local texture measurements; and ͑d͒ alignment of the beam position relative to the fiber orientation in the tissue makes it possible to resolve the local crystallite orientation quantitatively.…”
mentioning
confidence: 99%
“…These patterns have been ascribed to the apatite crystals regularly deposited in the gap zone, which stain the collagen fibrils (White et al, 1977;Ascenzi et al, 1985). The analysis of the small-angle reflections has been successfully utilized to study the distribution and orientation of collagen fibrils in single osteons and in lamellar bone (Ascenzi et al, 1998;Bigi et al, 1998). We have recently found that the small-angle X-ray diffraction reflections from teleost fish scales display the simultaneous presence of different orientations, which could correspond to a plywood arrangement of collagen fibrils in successive layers parallel to the plane of the scale (Bigi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%